Application of PCR-based approaches for evaluation of cell-free DNA fragmentation in colorectal cancer - Koval, Anastasia P.; Khromova, Alexandra S.; Blagodatskikh, Konstantin A.; Zhitnyuk, Yulia V.; Shtykova, Yanina A.; Alferov, Aleksandr A.; Kushlinskii, Nikolay E.; Shcherbo, Dmitry S. (Frontiers in Molecular Biosciences, 2023)
Cell-free DNA (cfDNA) testing is the core of most liquid biopsy assays. In particular, cfDNA fragmentation features could facilitate non-invasive cancer detection due to their interconnection with tumor-specific epigenetic alterations. However, the final cfDNA fragmentation profile in a purified sample is the result of a complex interplay between informative biological and artificial technical factors. In this work, we use ddPCR to study cfDNA lengths in colorectal cancer patients and observe shorter and more variable cfDNA fragments in accessible chromatin loci compared to the densely packed pericentromeric region. We also report a convenient qPCR system suitable for screening cfDNA samples for artificial high molecular weight DNA contamination.